Analisis Komunikasi: Efektivitas Qaulan Sadida Terhadap Dinamika Interpersonal - Mulyono; Azhar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
This research aims to determine the effectiveness of qaulan sadida on interpersonal dynamics. This research uses a qualitative descriptive method. In collecting data, researchers did this by means of non-participant observation as primary data and literature study as secondary data (literature review). In analyzing research data, researchers carry out reduction, presentation and verification stages or make conclusions. The results of this research show that the concept of qaulan sadida, which emphasizes honesty, gentleness, and respect for other people's opinions, has a positive impact on communication and interpersonal dynamics. By applying values such as sincerity, consistency, openness, and choosing wise words, individuals can build strong, trusting, and inclusive relationships. Qaulan sadida also helps avoid unnecessary conflict, creates an environment that supports mutual growth, and encourages acceptance of diversity. The application of this principle is not limited to a religious context, but can be applied in various aspects of daily life.